Transcriptome analysis of mesocarp tissues in oil palm (Elaeis guineessis jacq.) MPOB-angola dura across various developmental stages - Morris, Priscilla Elizabeth (2019)
Oil palm (Elaeis guineessis) Malaysian Palm Oil Board (MPOB) Angolan germplasm materials were evaluated for their potential use in oil palm breeding programmes. Large fruit characteristic of some Angola dura palms has provided breeders with a source of favourable traits for introgression into the current planting materials. With the aim of understanding molecular regulation during mesocarp development, maturation and ripening of Angola dura palms, efforts were initiated to profile the expression of transcripts across nine different developmental stages of mesocarp tissues. The second objective of this study was to identify differentially expressed genes associated with lipid metabolism, carbohydrate metabolism, transcription factors and plant hormone metabolism in mesocarp. The final objective was to profile the expression of selected WRINKLED1 transcripts across different developmental stages of mesocarp, endosperm and vegetative tissues. A total of 36,675 genes were identified from RNA-Sequencing with 24,226 transcripts successfully annotated with the Plant Reference Sequence Database using BLASTX. Pairwise T-test was performed using TIGR Multiexperiment Viewer and a total of 21,261 transcripts were identified as significantly differentially expressed across all the pairwise comparisons. BLAST2GO analysis assigned 13,996 unigenes with various GO terms. Transcripts associated with lipid metabolic process were highly expressed during lag phase preceding the lipid biosynthesis [(10 to 12 Week After Anthesis (WAA)] and fruit maturation (18 to 20 WAA) stages. Meanwhile, transcripts linked with carbohydrate metabolic process were up regulated during transition of fruit developmental stages from 10 to 12 WAA. Further annotation of the unigenes with KEGG pathway identified 279, 757 and 142 transcripts related to lipid, carbohydrate and hormone metabolisms, respectively. Additionally, plant RefSeq database annotated 272 transcripts encoding transcription factors. The most stable reference genes for RT-qPCR were selected based on RefFinder software. Twenty-seven transcripts from the RNA-Seq data of nine developmental stages associated with lipid, carbohydrate, plant hormone metabolism and transcription factors were chosen for validation of expression levels using Fluidigm 48.48 Real-Time qPCR. Transcripts such as KAS I, FATA, DGAT, ENR, WRI1 and bZIP showed different expression profiles in the MPOB-Angola dura as compared to the previously reported data. WRI1-2 was highly expressed in the mesocarp of MPOB-Angola dura at the beginning of oil accumulation from 20 WAA to 24 WAA with log2 (fpkm) of 4.7, together with the up-regulation of FA (and TAG biosynthetic genes In contrast, WRI1-4 was highly expressed in the endosperm of MPOBAngola dura from 8-15 WAA and decreased at 18 WAA with a fold change of 4.9 which corresponded with the expression profiles of KAS I in the endosperm tissues. The availability of these transcriptome datasets gives an insight into the transcriptional mechanisms controlling the Angolan dura fruit development, maturation and ripening.